Chemical composition and cytotoxic properties of Clinacanthus nutans root extracts - Teoh, Peik Lin; Cheng, Angelina Yi Fang; Liau, Monica; Lem, Fui Fui; Grace P. Kaling; Chua, Fern Nie; Cheong, Bo Eng (Informa Healthcare, 2017)
Context: Clinacanthus nutans Lindau (Acanthaceae) is a medicinal plant that has been reported to have anti-inflammatory, antiviral, antimicrobial and antivenom activities. In Malaysia, it has been widely claimed to be effective in various cancer treatments but scientific evidence is lacking.